Review of the natural conditions and anthropogenic threats to the Ethiopian Rift Valley rivers and lakes. Issue 2 (June 2016) - Lemma, Brook; Desta, Hayal
Abstract: This review article considers the lakes found within the Ethiopian Rift Valley system and the rivers draining from the highlands towards them. The Ethiopian Rift Valley system extends in a north‐east–south‐west direction, bisecting the Ethiopian highlands. They differ in sizes and hydrological and hydrogeological settings. The lakes support a variety of flora and fauna, mainly fishes, reptiles, birds and mammals. The lakes and their feeder rivers, however, are currently being subjected to more human use pressure than previously experienced, attributable mainly to water abstractions for irrigation, household water supply and industrial activities in the catchments. Soil erosion, primarily attributable to the lack of soil conservation practices on farm lands, overgrazing and deforestation, along with unregulated irrigation practices, are generating large quantities of silt reaching the lakes. Improper utilization of water and land resources in the catchments, along with population growth and climate change impacts, is escalating the threats to the health of the lake and river ecosystems. As a result, some of the lakes exhibited reduced water levels and increased salinity. This article reviews the major environmental changes happening to these lakes and their feeder rivers. Visits were made to the area to update previous information while also consolidating the trends of change in the aquatic systems and the watersheds attributed to intense development practices.